High magnetoresistance at low magnetic fields in self-assembled ZnO–Co nanocomposite films. Issue 29 (13th July 2017) - Jedrecy, N.; Hamieh, M.; Hebert, C.; Perriere, J.
Abstract : Very small ferromagnetic Co nanoclusters embedded in a crystalline ZnO matrix lead to high values of magnetoresistance with good field-sensitivity. Abstract : The solid phase growth of self-assembled nanocrystals embedded in a crystalline host matrix opens up wide perspectives for the coupling of different physical properties, such as magnetic and semiconducting. In this work, we report the pulsed laser growth at room temperature of thin films composed of a dispersed array of ferromagnetic Co (0001) nanoclusters with an in-plane mono-size width of 1.3 nm, embedded in a ZnO (0001) crystalline matrix. The as-grown films lead to very high values of magnetoresistance, ranging at 9 T from −11% at 300 K to −19% at 50 K, with a steep decrease of the magnetoresistance at low magnetic fields. We establish the relationship between the magnetoresistance behavior and the magnetic response of the Co nanocluster assembly. A spin-dependent tunneling of the electrons between the Co nanoclusters through and by the semi-insulating ZnO host is achieved in our films, promising with regard to magnetic field sensors or Si-integrated spintronic devices. The effects of thermal annealing are also discussed.